Detection of lupus erythematosus cells in pleural effusion: An unusual presentation of systemic lupus erythematosus - Gulhane, Sushma (Medknow Publications & Media Pvt Ltd, 2012)
Systemic lupus erythematosus (SLE) is a chronic inflammatory disease typically diagnosed by a combination of physical findings and clinical laboratory testing. Several decades ago, the diagnosis of lupus included the lupus erythematosus (LE) cell assay. SLE is associated with pleuropulmonary manifestations in well over 50% of cases. Although pleural effusion is common but very rarely is the initial manifestation of disease. There are very few reports of SLE diagnosed in a cytopathology laboratory. We report an unusual case of SLE in a 16-year-old female who presented with acute shortness of breath, fever and cough. Her chest radiograph showed bilateral pleural effusion. This effusion was tapped and sent to the cytopathology laboratory. The cytological examination of the pleural fluid revealed numerous LE cells and led to the diagnosis of SLE. Autoimmune serology techniques such as anti-nuclear antibody staining have replaced the LE cell assay. However, as presented in this report and found in a review of the literature, the in vivo finding of LE cells by cytopathology can provide an important clue to the diagnosis of SLE, especially when associated with an uncommon presentation.